Policy, service, and training provision for women following a traumatic birth: an international knowledge mapping exercise - Thomson, Gill; Diop, Magali Quillet; Stuijfzand, Suzannah; Horsch, Antje; Lalor, Joan G.; De Abreu, Wilson; Avignon, Valérie; Baranowska, Barbara; Dikmen-Yildiz, Pelin; El Hage, Wissam; Fontein-Kuipers, Yvonne; Horsch, Antje; et al. (My University, 2021)
High numbers of women experience a traumatic birth, which can lead to childbirth-related post-traumatic stress disorder (CB-PTSD) onset, and negative and pervasive impacts for women, infants, and families. Policies, suitable service provision, and training are needed to identify and treat psychological morbidity following a traumatic birth experience, but currently there is little insight into whether and what is provided in different contexts. The aim of this knowledge mapping exercise was to map policy, service and training provision for women following a traumatic birth experience in different European countries.
Keywords: Education; Policy; Services; Survey; Training; Traumatic birth